Genetic Diversity of Selective Breeding Populations of Giant Freshwater Prawn (Macrobrachium rosenbergii) Based on SSR and Mitochondrial D-Loop Gene - Salifu Ibrahim; Amin Ruhul; Jingfen Li; Guoliang Yang; Shaokui Yi; Zhenglong Xia; Miaoying Cai; Yuewen Deng; Qiongying Tang (Diversity)
Macrobrachium rosenbergii, commonly known as giant freshwater prawns (GFPs), is an economically and nutritionally important decapod crustacean species in China. Understanding the genetic diversity of selective breeding populations is crucial in breeding plans for selecting genetically diverse broodstocks and maintaining genetic diversity. The genetic structure of six breeding populations (Hefu (HF), Nantaihu No.2 (NTH), Jiaxin (JX), Shufeng (SF), Taiwan (TW), and Guangxi (GX)) of GFP in China was examined using 16 newly developed microsatellite loci and the mitochondrial control region (D-loop). The microsatellite data revealed that all 16 loci have high diversity, with all values of polymorphism information content (PIC) more than 0.5. The average expected heterozygosity (He, 0.89) and the number of alleles (Na, 18.25) of SF were the highest, followed by He (0.89) and Na (14.75) of the JX, and GX has the lowest He (0.83) and Na (11.31). The average PIC value for the six stocks ranged from 0.80 to 0.87. Pairwise comparisons revealed that Fst ranged from 0.03541 to 0.09637 and was significant (p < 0.05) between most populations, indicating from low to moderate genetic differentiation among the six populations. The D-loop analysis identified 114 variable sites and 29 haplotypes, with an average haplotype diversity (Hd) and nucleotide diversity (π) of 0.640 and 0.01247, respectively. Genetic differentiation among the six populations based on the D-loop was from moderate to high, with Fst values of 0.05603–0.80788, and all p < 0.05. This study demonstrates that selective breeding stocks of M. rosenbergii in China show moderate to high genetic diversity and have the potential for further selective breeding, providing a theoretical basis for conserving and utilizing M. rosenbergii genetic resources.